Navigating economic fragility and climate risk: Transformative pathways to eco-welfare in vulnerable coastal ecosystems - Mst. Roksana Akter; Moudud Ahmad; Shamima Akter; Habiba Akther Jakia; Md. Kamrul Hasan (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: In Hatiya Upazila, Noakhali District, Bangladesh, a coastal area vulnerable to one to three yearly disasters as well as risks like tidal waves, floods, and river erosion, this study examines climate risk and community-driven resilience. Method: This study was conducted in four villages in Hatiya Upazila, namely Nalchira, Chariswar, Jahajmara, and Nijhum Dwip, which were selected due to their geographical vulnerability and socio-economic diversity. Data were collected through triangulation of primary sources, including 12 interviews with key informants, 12 thematic case studies, and 12 focus group discussions, as well as secondary government statistics. Analysis was conducted using iterative thematic coding and subjective interpretation to synthesize field observations and individual narratives into insights on local resilience. Finding: The results show extreme economic fragility, with 80% of households using ways to cope, like cutting back on meals and buying food on loan, to deal with malnutrition. The majority of the population, who make between BDT 4,000 and 4,500 a month, rely on daily employment, fishing (21%), and agriculture (20%), all of which are hampered by severe weather. Raised plinths, income diversification (e.g., livestock rearing, handicrafts), and water management are examples of adaptable behaviors; but susceptibility is made worse, especially for women, by a lack of availability of alert systems, health services, and education. Conclusion: Recommendations include strengthening early warning systems, promoting sustainable livelihoods, and improving infrastructure like storm shelters and sanitation. Leveraging Hatiya’s productive fisheries and fields can enhance resilience and serve as a model for other climate-sensitive regions. Novelty/Originality of this article: This study highlights the critical role of local governance, informal leadership, and social networks in shaping resilience. It suggests that adaptation is most effective when integrating indigenous knowledge with structured community coordination, offering a more dynamic perspective on long-term climate survival.